2009
DOI: 10.1098/rspb.2009.1458
|View full text |Cite
|
Sign up to set email alerts
|

Conservative ecological and evolutionary patterns in liverwort–fungal symbioses

Abstract: Liverworts, the most ancient group of land plants, form a range of intimate associations with fungi that may be analogous to the mycorrhizas of vascular plants. Most thalloid liverworts contain arbuscular mycorrhizal glomeromycete fungi similar to most vascular plants. In contrast, a range of leafy liverwort genera and one simple thalloid liverwort family (the Aneuraceae) have switched to basidiomycete fungi. These liverwort switches away from glomeromycete fungi may be expected to parallel switches undergone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 38 publications
(64 reference statements)
2
55
0
1
Order By: Relevance
“…examined to date with the exception of A. pellioides (Horik.) and A. pinguis from California (Bidartondo & Duckett 2010), the sister genus Riccardia Gray is almost fungus-free. In three Riccardia taxa, all New Zealand endemics, where an endophyte is present the associations appear distinctively different from those in Aneura.…”
Section: Ascomycetes In the Jungermanniopsidamentioning
confidence: 99%
See 3 more Smart Citations
“…examined to date with the exception of A. pellioides (Horik.) and A. pinguis from California (Bidartondo & Duckett 2010), the sister genus Riccardia Gray is almost fungus-free. In three Riccardia taxa, all New Zealand endemics, where an endophyte is present the associations appear distinctively different from those in Aneura.…”
Section: Ascomycetes In the Jungermanniopsidamentioning
confidence: 99%
“…(Bidartondo et al 2003;Kottke et al 2003) indicate that the aneuracean associations are of recent origin. Much more extensive sequencing investigations (Bidartondo & Duckett 2010;Preußing et al 2010), embracing over one hundred collections of the Aneuraceae, revealed that whilst in the vast majority the fungus is Tulasnella, two gatherings (from Chile and Switzerland) contained Sebacina Tul., the basidiomycete genus characteristic of leafy liverworts (Kottke et al 2003). The molecular diversity discovered within the Tulasnella symbionts (Bidartondo & Duckett 2010;Preußing et al 2010), plus the rare occurrence of sebacinoids, in seemingly closely allied aneuracean taxa was at first sight most surprising.…”
Section: Ascomycetes In the Jungermanniopsidamentioning
confidence: 99%
See 2 more Smart Citations
“…Newsham and Bridge (2010) found that Sebacinales associates of the leafy liverwort Lophozia excisa in the southern maritime Antarctic represent the sister group of sebacinalean mycobionts of European Lophozia and Calypogeia species. Basidiomycetous mycobionts of 30 liverwort species from worldwide locations were analyzed by Bidartondo and Duckett (2010). Species of Barbilophozia, Calypogeia, Diplophyllum, Lophozia, Nardia, Sarcogyna, Scapania, Southbya, and Tritomaria, members of the Jungermanniales, were associated with taxa of the S. vermifera complex.…”
Section: Mycorrhizal Network and Species Richness Of Sebacinales Inmentioning
confidence: 99%